3-Chloro-quinuclidinium chloride. - Azizul, I.; Zainudin, A.; Ng, S.W. (International Union of Crystallography, 2008)
The cation of the title compound, C(7)H(13)ClN(+)·Cl(-), forms a linear hydrogen bond to the chloride anion. The cation is disordered about a mirror plane.